Tools of Decision Making in the Field of strategic advertisement of pharmaceutical Enterprises - Burkynskyi, B.V.; Sokolovska, Z.M.; Alyokhin, A.B.; Khumarova, N.I.; Kapustyan, I.V. (Наука та інновації, 2020)
Introduction. The evolution of the modern information and communication technologies contributes to enhancement of advertising strategies, as effective tools of pharmaceutical marketing. Problem Statement. The need to take into account the nonlinear dynamic nature of advertising processes and presence the influence of numerous stochastic factors in market environment of pharmaceutical enterprises with the impossibility of obtaining an unambiguous analytical solution put forward problem of attracting a special mathematical apparatus for research. Purpose. To study processes of decision-making in the field of strategic advertising of pharmaceutical enterprises using the apparatus of simulation modeling. Materials and Methods. The research is based on using multi approach paradigm of simulation in the software environment of AnyLogic. The materials of pharmaceutical company OJSC "Farmak" are used in the course of simulation experiments. Results. The expediency of attracting modeling methods as tools of making strategic advertising decisions is substantiated. A simulation model-simulator is proposed, developed using a combination of Agent and System- Dynamic approaches on the AnyLogic software platform. The decision-making process is illustrated by the results of various types of simulation experiments. The main areas of use the simulator: monitoring and predicting the reaction of target audiences to product advertising; effectiveness control of research on new and re-releasing existing medicines in response to market reactions and preferences of potential clients; optimization of advertising budget with justification of expediency of its redistribution between original and generic preparations. Conclusions. The efficiency of using simulation models-simulators as tools for the formation of advertising strategies has been proved. The development can be recommended for implementation by pharmaceutical companies. Вступ. Розвиток сучасних інформаційно-комунікаційних технологій сприяє удосконаленню рекламних стратегій, як ефективних інструментів фармацевтичного маркетингу. Проблематика. Необхідність врахування нелінійного динамічного характеру рекламних процесів, наявності впливу численних стохастичних факторів ринкового оточення фармацевтичних підприємств при неможливості отримання однозначного аналітичного рішення актуалізують проблему залучення спеціального математичного апарату дослідження. Мета. Дослідити процеси прийняття рішень в галузі стратегічної реклами фармацевтичних підприємств з використанням апарату імітаційного моделювання. Матеріали й методи. Дослідження базується на використанні багатопідходної парадигми імітаційного моделювання в програмному середовищі системи AnyLogic. Як аналітичний матеріал використано дані фармацевтичної компанії ВАТ «Фармак». Результати. Обґрунтовано доцільність залучення методів імітації як інструментів прийняття стратегічних рекламних рішень. Запропоновано імітаційну модель-тренажер, розроблену з використанням комбінації агентного та системно-динамічного підходів на програмній платформі AnyLogic. Процес прийняття рішень проілюстровано результатами різних типів імітаційних експериментів. Окреслено основні напрямки використання моделі-тренажера: моніторинг і прогнозування реакції цільових аудиторій на товарну рекламу; контроль ефективності досліджень нових та перевипуску існуючих препаратів згідно з реакцією ринку та вподобаннями потенційних клієнтів; оптимізація рекламного бюджету з обґрунтуванням доцільності його перерозподілу між оригінальними та генеричними препаратами. Висновки. Доведено ефективність використання імітаційних моделей-тренажерів як інструментів формування рекламних стратегій. Розробку може бути рекомендовано для впровадження фармацевтичними компаніями.